Wish you were dead - Strasser, Todd (Egmont USA, 2009)
Madison, a senior at a suburban New York high school, tries to uncover who is responsible for the disappearance of her friends, popular students mentioned in the posts of an anonymous blogger, while she, herself, is being stalked online and in-person.